An interior point approach for linear complementarity problem using new parametrized kernel function. (9th December 2022) - Benhadid, Ayache; Saoudi, Khaled; Merahi, Fateh
Abstract : In this paper, we propose a primal–dual interior point method for Linear Complementarity Problem (LCP) based on a new parameterized kernel function. The investigation according to it yields the best-known iteration bound O ( n log ⁡ ( n ) log ⁡ ( n ϵ ) ) for large-update algorithm and thus improves the iteration bound obtained in Bai et al. (SIAM J Optim. 2004;15:101–128) for large-update algorithm. Finally, we present few numerical results to demonstrate the efficiency of the proposed algorithm.